USE OF INNOVATIVE TECHNOLOGIES IN MOTHER LANGUAGE LESSONS - Azimova Nigora (Web of Journals Publishing, 2023)
The article discusses the innovative pedagogical technologies and methods used in the education system today. The importance of increasing the effectiveness of mother tongue classes was discussed.
Keywords: pedagogical technology, method, innovation, sentence fragments, section.